The Effect of the SAVI Learning Model on Character Building in Elementary Students - Muhammad Hafiz; Mardianto Mardianto; Abdul Hafizh Azizi Batubara; Abdul Rasyid Rosandi Lubis; Nur Atika; Najaruddin Butar-Butar; Rahmad Anwi Siregar (Universitas Pahlawan Tuanku Tambusai, 2023)
Low self-confidence is one of the problems faced by students in the learning process, so that the teacher's efforts are needed to facilitate the improvement of character building in students. This study aims to determine the effect of the SAVI (Somatic, Auditory, Visualization, and Intellectuality) learning model in increasing elementary-aged students' self-confidence. This research was conducted in class VII MTs Yaspend Muslim, with a sample of class VII-3 students. Data analysis used a type of regression analysis. The results of this study found that the effect of the SAVI model on student character building was in the good category, with the Fcount regression test of 37.59 and Ftable of 4.18. Thus, it can be concluded that the SAVI learning model (Somatic, Auditory, Visualization, and Intellectualy) has a positive effect on students' Character Building, because this learning model involves all students' sensory modalities so that students become active.